Corporate tax aggression and debt - Lin, Shannon; Tong, Naqiong; Tucker, Alan L. (Journal of Banking & Finance, 2014)
We provide a tradeoff model of the capital structure that allows leverage to be a function of a firm’s choice of tax aggressiveness. The model’s testable implications are supported empirically. Debt use is inversely related to corporate tax aggression for most firms, and the relation is economically important. This substitution effect is especially evident for firms exhibiting high tax-shelter prediction scores. The effect attenuates for benign forms of tax avoidance and during the recent credit crisis period. For the most profitable firms, debt and tax aggression are complements. Our results extend the empirical findings of Graham and Tucker (2006).